2021
DOI: 10.1002/jeab.717
|View full text |Cite
|
Sign up to set email alerts
|

The selective action of Cfunc control

Abstract: According to relational frame theory Cfunc stimuli select which stimulus properties are transformed via derived stimulus relations. To date there has been no demonstration of the selective action of Cfunc control. We provide an analysis of the requirements for such a demonstration, and describe the results from four experiments employing a paradigm consistent with these requirements. We employed a paradigm based on virtual car races. The paradigm had two components: i) a sample racecar screen which showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Both implications are well-supported. On the one hand, research has shown that relational responding can be brought under operant control, both in terms of the specific types of relational responses that people emit (i.e., Crel control; Hughes et al, 2019;Perez et al, 2017) as well as the specific properties of stimuli which people relate (i.e., Cfunc control; Delabie et al, 2022;Finn & De Houwer, 2021). On the other hand, there are now many studies which demonstrate that relational responding fluency can be trained directly (Cassidy et al, 2016;Colbert et al, 2018;McLoughlin et al, 2021).…”
mentioning
confidence: 99%
“…Both implications are well-supported. On the one hand, research has shown that relational responding can be brought under operant control, both in terms of the specific types of relational responses that people emit (i.e., Crel control; Hughes et al, 2019;Perez et al, 2017) as well as the specific properties of stimuli which people relate (i.e., Cfunc control; Delabie et al, 2022;Finn & De Houwer, 2021). On the other hand, there are now many studies which demonstrate that relational responding fluency can be trained directly (Cassidy et al, 2016;Colbert et al, 2018;McLoughlin et al, 2021).…”
mentioning
confidence: 99%